2021
DOI: 10.18844/gjflt.v11i1.5339
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Willingness to Speak Chinese: Case of Transferring Learning Chinese into Communication among University of Ghana Students.

Abstract: Willingness to communicate (WTC) has become an important role that facilitate language learning, the aim of this paper is to investigate WTC in Chinese as foreign language of motivation to transfer learning through oral communication among students learning Chinese at the university of Ghana. Second language learner’s motivation to transfer learning is grounded on effort, desire, knowledge, and skills learned in classroom and beyond the classroom to achieve the goal of learning a language.   By adopting a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For example, Liu (2017) investigated adult Chinese as a second language (CSL) learners' WTC in Chinese and found their WTC was determined by speaking anxiety and length of stay in China. Nkrumah (2021) also found that the environment and teaching practices influenced CSL learners' WTC. However, aside from Hosseinpur and Nevisi (2017), which found a positive relation between pragmatic production and WTC, few studies have investigated the relationship between pragmatic competence and WTC.…”
Section: Introductionmentioning
confidence: 88%
“…For example, Liu (2017) investigated adult Chinese as a second language (CSL) learners' WTC in Chinese and found their WTC was determined by speaking anxiety and length of stay in China. Nkrumah (2021) also found that the environment and teaching practices influenced CSL learners' WTC. However, aside from Hosseinpur and Nevisi (2017), which found a positive relation between pragmatic production and WTC, few studies have investigated the relationship between pragmatic competence and WTC.…”
Section: Introductionmentioning
confidence: 88%
“…They enter the learning environment with different and sometimes conflicting cultures and subcultures ( Lee and Lee, 2020 ). They do not just try to express themselves, but their goal is to influence their audience ( Nkrumah, 2021 ). In other words, by talking, they want the audience to understand what they mean.…”
Section: Introductionmentioning
confidence: 99%
“…The need for communication is one of the most important things in a person's life (Nkrumah et al, 2021). When we enter relationships with the world around us, we communicate information about ourselves, in return we receive information that interests us, analyze it, and plan our activities in society based on this analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing research in this area of child psychology, Mukhina notes that in the sphere of "child -adult" and "child -parents" there are new relationships "child-teacher", raising the child to the level of social requirements for his behavior. In a teacher for a schoolchild, the normative requirements are implemented with more certainty than in a family, because in the primary conditions of communication it is difficult to distinguish oneself and evaluate the nature of one's behavior (Nkrumah, 2021). Only the teacher who makes demands on the school child, evaluating his behavior, creates normal conditions for the child's life in society.…”
Section: Introductionmentioning
confidence: 99%